Dor crônica na coluna vertebral e variabilidade da frequência cardíaca em sedentários: comparações entre cervicalgia e lombalgia - SILVA , André Pontes (2021)
Introduction: heart rate variability (HRV) has been used for studies of the human nervous system in various health and disease situations, however, there is no research comparing HRV in different chronic conditions of the spine. Objective: to compare HRV between patients with chronic neck pain and patients with chronic low back pain. Secondarily, to correlate the variables of chronic pain with HRV indices. Methods: the sample of this study was divided into group CNP (chronic neck pain, n = 30) and group LBP (chronic low back pain, n = 30). We used the following instruments for pain assessment: Numerical Rating Scale, Neck Disability Index, Roland-Morris Disability Questionnaire, Pain-Related Catastrophizing Thoughts Scale, Tampa Scale of Kinesiophobia and Pain Self-Efficacy Questionnaire. For HRV analysis, we used the following indexes: mean RR, STD-RR, mean HR, rMSSD, RR Tri, TINN, LF, HF, SD1, SD2 and Stress Index. Results: chronic low back pain is more disabling than chronic neck pain; however, the disability generated by chronic neck pain in this study is associated with the worst HRV rates. We identified statistical differences (p < 0.05) and moderate clinical effect (d > 0.50) in SD2/SD1 in supine, and mean RR and mean HR in standing, with worse indexes in group 1. Disability and HRV indexes only correlated in group 1 (p < 0.05, with a magnitude of correlation ranging from weak to moderate). Conclusions: patients with chronic neck pain, when compared to patients with chronic low back pain, have less sympatheticvagal balance, less variability in RR intervals and higher heart rate. Disability and self-efficacy were correlated with HRV only in patients with chronic neck pain, while catastrophizing and kinesiophobia showed greater correlations with HRV in patients with chronic low back pain.